Impact of a structured educational programme for caregivers of children with cancer on parental knowledge of the disease and paediatric clinical outcomes during the first year of treatment. (24th July 2020) - De la Maza, Verónica; Manriquez, Macarena; Castro, Magdalena; Viveros, Paola; Fernandez, María; Vogel, Evelyn; Peña, Erica; Santolaya, María Elena; Villarroel, Milena; Torres, Juan Pablo
Abstract: Objective: To assess the impact of a structured educational programme for caregivers of children with cancer on their level of knowledge about the disease and patient's clinical outcome. Methods: This prospective, non‐randomised, experimental study included caregivers of recently diagnosed children at two hospitals in Chile. Caregivers whose children were treated at the first centre were the structured education programme group (EPG), while the second hospital provided the standard care (SCG). We evaluated caregivers' level of knowledge on days 1, 10 and 90 as well as the children's clinical outcomes over 1 year of treatment. Results: A total of 102 caregivers were enrolled between 2014 and 2015. Only the EPG showed a significant increase in knowledge between days 1 and 90. The rate of central venous catheter infections was significantly lower in the EPG versus SCG (7% versus 26%; p  = .01). The risk ratio was 0.35 (95% CI = 0.13–0.94), and a log‐rank test showed a statistically significant difference between the two groups ( p  = .018). There were also fewer Emergency Department visits in the EPG for fever episodes. Conclusion: Providing a structured education to caregivers increased their level of knowledge and improved the clinical outcome of their children during the first year of treatment.